A high-toughness ceramic dielectric material and preparation method thereof

Through the combination of Bi4Ti2.92W0.07Ta0.01O12-type ceramic material with glass powder and sodium alginate, ball milling and freeze-drying processes are adopted to solve the problem of insufficient mechanical properties of low-temperature co-fired ceramic materials, and high toughness and excellent dielectric properties are achieved. The preparation of ceramic dielectric materials meets the needs of modern electronic information technology.

CN116639973BInactive Publication Date: 2024-12-17TAIYUAN NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310692430.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-01
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The mechanical properties of existing low-temperature co-fired ceramic materials are insufficient, which is difficult to meet the development needs of modern electronic information technology, especially in the process of chemical mechanical polishing and packaging, which is difficult to withstand large mechanical forces.

Method used

Using Bi4Ti2.92W0.07Ta0.01O12-type ceramic material combined with glass powder and sodium alginate solution, ceramics with high toughness, high dielectric constant and low dielectric loss were prepared through ball milling, vacuum defoaming, directional freeze-drying and other processes. Dielectric material.

Benefits of technology

The high toughness and excellent dielectric properties of ceramic dielectric materials are achieved, the sintering temperature is reduced, and the porous layered structure is formed to absorb fracture energy, which improves the temperature stability and performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BSA0000297058380000031
    Figure BSA0000297058380000031
  • Figure BSA0000297058380000041
    Figure BSA0000297058380000041
  • Figure BSA0000297058380000051
    Figure BSA0000297058380000051
Patent Text Reader

Abstract

The invention discloses a high-toughness ceramic dielectric material, comprising the following raw materials in percentage by mass: 10-30% glass powder, Bi4Ti 2.92 W 0.07 Ta 0.01 O 12 70-90%. The glass powder includes the following raw materials in percentage by mass: MgO 5-40%, SiO25-30%, CeO25-30%, Al2O35-30% and AlF35-30%. The present invention adopts the method of adding glass powder and freeze drying, which not only reduces the sintering temperature but also forms a porous layered structure. The ceramic dielectric material has high toughness, high dielectric constant, low dielectric loss and high temperature stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention discloses a high-toughness ceramic dielectric material and a preparation method thereof, belonging to the technical field of ceramic dielectric materials. Background Art

[0002] Low-temperature co-fired ceramic technology was first introduced by the United States in the mid-1980s. This technology integrates passive devices and packaging and is a multi-layer ceramic manufacturing technology. Low-temperature co-fired ceramic technology uses thick film material technology. The main method of this technology is to sinter electronic components into a pre-designed structure at one time.

[0003] The so-called low-temperature co-fired ceramic technology is to make low-temperature sintered ceramic powder into a green porcelain tape with precise thickness and density as a circuit substrate material. The required circuit pattern is made on the green porcelain tape by laser drilling, micropore grouting, precision conductor slurry printing and other processes, and multiple passive components (such as transformers (T), resistors (R), inductors (L), capacitors (C)) are buried in it, and then stacked together and sintered below 900°C to make passive integrated components of three-dimensional circuit networks. It can also be made into a three-dimensional circuit substrate with built-in passive components. ICs and active devices can be mounted on its surface to make passive / active integrated functional modules, thereby realizing the miniaturization, lightweight, high-performance and multi-functional design of electronic components and packaging modules.

[0004] Low-temperature co-fired ceramic material technology has become an irreplaceable and important foundation for the development of high-density packaging and electronic component integration, miniaturization, lightweight, and high reliability. At present, most of the research on low-temperature co-fired ceramic materials is focused on ceramic materials with different dielectric constants, and the most reported ones are BaO-Ln2O3-TiO2 (Ln is a rare earth element), BaTi4O9, Al2O3, etc., while the research on the mechanical properties of ceramic materials is relatively lagging behind and it is difficult to meet the development needs of modern electronic information technology, such as whether the chemical mechanical polishing and packaging process can withstand large mechanical forces.

[0005] Therefore, from the perspective of material serialization and reducing the size of electronic components, researching and developing ceramic materials with excellent properties such as high toughness, high dielectric constant, and low loss that can be co-fired at low temperature with electrode materials such as silver and copper is of great significance to promoting the development of modern electronic information technology. Summary of the invention

[0006] In order to solve the deficiencies in the prior art, the present invention discloses a high-toughness ceramic dielectric material and a preparation method thereof. The ceramic dielectric material has high toughness, high dielectric constant, low dielectric loss and high temperature stability.

[0007] The present invention is achieved through the following technical solutions:

[0008] A high-toughness ceramic dielectric material includes the following raw materials in percentage by mass: 10-30% glass powder, Bi4Ti 2.92 W 0.07 Ta 0.01 O 12 70-90%.

[0009] The glass powder comprises the following raw materials in percentage by mass: MgO 5-40%, SiO2 5-30%, CeO2 5-30%, Al2O3 5-30% and AlF3 5-30%.

[0010] A method for preparing a high-toughness ceramic dielectric material comprises the following steps performed in sequence:

[0011] 1) Raw materials Bi2O3, WO3, Ta2O5 and TiO2 are prepared according to the general formula Bi4Ti 2.92 W 0.07 Ta 0.01 O 12 Weigh the ingredients in the chemical stoichiometric ratio, ball mill them, and pass through 120-250 pores / cm 2 Sieve the sample, raise the temperature to 1000-1100℃, keep it warm for 2-4 hours, and obtain frit A;

[0012] 2) melting MgO 5-40%, SiO2 5-30%, CeO2 5-30%, Al2O3 5-30% and AlF3 5-30% according to mass percentage, cooling with water, grinding and sieving to obtain glass powder B;

[0013] 3) 10-30% of glass powder B and 70-90% of frit A are mixed according to mass percentage to obtain mix C;

[0014] 4) preparing a sodium alginate solution by mixing 2% sodium alginate and 98% deionized water according to mass percentage;

[0015] 5) adding 70-80% by mass of sodium alginate solution and 2-5% by mass of ammonium citrate to ingredient C, ball milling, vacuum degassing, and directional freeze drying;

[0016] 6) After drying, the green body is slowly heated to 830-860° C. in an air atmosphere and kept at that temperature for 1 hour, and then cooled to obtain a ceramic medium.

[0017] In the step 1), the ball milling time is 4-6 hours, and the ball milling medium is a zirconia ball with a diameter of 1 mm.

[0018] The heating rate in step 1) is 7-9°C / min.

[0019] In the step 5), the freezing temperature is -10°C, -30°C, or -50°C, and the directional freezing time is 5-8 hours.

[0020] The drying time in step 5) is 20-23 hours.

[0021] The heating process in step 6) is divided into two stages: the first stage is heating from room temperature to 400-500°C at a heating rate of 2-5°C / min; the second stage is heating from 400-500°C to 830-860°C at a heating rate of 5-8°C / min.

[0022] Compared with the prior art, the present invention has the following beneficial effects: 2.92 W 0.07 Ta 0.01 O 12 The dielectric ceramic has a moderate sintering temperature, generally around 1100°C, a typical layered structure and a high dielectric constant. In addition, it has an adjustable capacitance temperature coefficient and low loss, and is a dielectric ceramic material with good performance. 2.92 W 0.07 Ta 0.01 O 12 The system adopts the method of adding glass powder and freeze drying, which not only reduces the sintering temperature but also forms a porous layered structure, thereby absorbing the fracture energy to achieve high toughness and excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The present invention will be further described below in conjunction with the accompanying drawings.

[0024] Figure 1 The test results of the temperature coefficient TCC of the ceramic dielectric materials prepared in Example 1, Example 2, Example 3 and Example 4 are shown in the figure. It can be seen from the figure that as the temperature increases, the temperature coefficient shows a slow upward trend as a whole, but the temperature coefficient is within ±15%, achieving a high temperature stability. DETAILED DESCRIPTION

[0025] The present invention is further described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to these embodiments, and any changes or equivalent substitutions that do not deviate from the concept of the present invention are included in the protection scope of the present invention.

[0026] Example 1

[0027] A high-toughness ceramic dielectric material includes the following raw materials in percentage by mass: 10% glass powder, Bi4Ti 2.92 W 0.07 Ta 0.01 O 1290%, the glass powder comprises the following raw materials in percentage by mass: MgO 5%, SiO2 30%, CeO2 30%, Al2O3 30% and AlF3 5%.

[0028] The preparation process is as follows:

[0029] 1) Raw materials Bi2O3, WO3, Ta2O5 and TiO2 are prepared according to the general formula Bi4Ti 2.92 W 0.07 Ta 0.01 O 12 , mix the ingredients, grind them in a ball mill at a speed of 400r / min for 4 hours, dry them in a 3.3kw ordinary oven at 100℃, and pass through 120 holes / cm 2 The sample was sieved, the temperature was raised to 1000°C at a rate of 7°C / min, and the temperature was kept at 1000°C for 2 hours to obtain frit A.

[0030] 2) Weigh 5 g of MgO, 30 g of SiO2, 30 g of CeO2, 30 g of Al2O3 and 5 g of AlF3, mix, melt and cool with water, grind and sieve to obtain glass powder B.

[0031] 3) Mixing the ingredients: weigh the frit A and the glass powder B in a mass ratio of 90% of the frit A and 10% of the glass powder B, mix them evenly, and obtain a batch C.

[0032] 4) Sodium alginate and deionized water were weighed in a mass ratio of 2% sodium alginate to 98% deionized water to prepare a sodium alginate solution.

[0033] 5) Weigh the sodium alginate solution and ammonium citrate according to the mass ratio of 70% sodium alginate solution and 2% ammonium citrate of ingredient C, add ingredient C, ball mill for 10 hours on a ball mill with a rotation speed of 400r / min, and place the slurry under vacuum conditions for 30 minutes for vacuum degassing. Inject the degassing slurry into a homemade mold, put it into a dryer and control the freezing temperature to -10°C, -30°C, and -50°C, respectively, and freeze it for 5 hours. Take out the mold and demould it quickly, and put it into a freeze dryer for sublimation for 20 hours.

[0034] 6) After drying, the green body is heated to 400°C at a heating rate of 2°C / min in an air atmosphere, and then heated to 830°C at a heating rate of 5°C / min, fired, kept warm for 1 hour, and cooled to obtain a ceramic medium.

[0035] The dielectric properties of the ceramic medium prepared in this embodiment were tested at a test frequency of 1 MHz. The results are shown in Tables 1 and Figure 1 .

[0036] Table 1

[0037]

[0038] Example 2

[0039] A high-toughness ceramic dielectric material includes the following raw materials in percentage by mass: 15% glass powder, Bi4Ti 2.92 W 0.07 Ta 0.01 O 12 85%, the glass powder comprises the following raw materials in percentage by mass: MgO 40%, SiO2 5%, CeO2 5%, Al2O3 20% and AlF3 30%.

[0040] The preparation process is as follows:

[0041] 1) Raw materials Bi2O3, WO3, Ta2O5 and TiO2 are prepared according to the general formula Bi4Ti 2.92 W 0.07 Ta 0.01 O 12 , mix the ingredients, grind them in a ball mill at a speed of 400r / min for 5 hours, dry them in a 3.3kw ordinary oven at 100℃, and pass through 200 holes / cm 2 The sample was sieved, the temperature was raised to 1050°C at a rate of 7°C / min, and the temperature was kept at 1050°C for 3 hours to obtain frit A.

[0042] 2) Weigh 40 g of MgO, 5 g of SiO2, 5 g of CeO2, 20 g of Al2O3 and 30 g of AlF3, mix, melt, water-cool, grind and sieve to obtain glass powder B.

[0043] 3) Mixing the ingredients: weigh the frit A and the glass powder B in a mass ratio of 85% of the frit A and 15% of the glass powder B, and mix them evenly to obtain a batch C.

[0044] 4) Sodium alginate and deionized water were weighed in a mass ratio of 2% sodium alginate to 98% deionized water to prepare a sodium alginate solution.

[0045] 5) Weigh the sodium alginate solution and ammonium citrate according to the mass ratio of 75% sodium alginate solution and 3% ammonium citrate of ingredient C, add ingredient C, ball mill for 10 hours on a ball mill with a rotation speed of 400r / min, and place the slurry under vacuum conditions for 30 minutes for vacuum degassing. Inject the degassing slurry into a homemade mold, put it into a dryer and control the freezing temperature to -10°C, -30°C, and -50°C, respectively, and freeze it for 6 hours. Take out the mold and demould it quickly, and put it into a freeze dryer for sublimation for 21 hours.

[0046] 6) After drying, the green body is heated to 450° C. at a heating rate of 3° C. / min in an air atmosphere, and then heated to 840° C. at a heating rate of 6° C. / min, sintered, kept warm for 1 hour, and cooled to obtain a ceramic medium.

[0047] The dielectric properties of the ceramic medium prepared in this embodiment were tested at a test frequency of 1 MHz. The results are shown in Tables 2 and Figure 1 .

[0048] Table 2

[0049]

[0050] Example 3

[0051] A high-toughness ceramic dielectric material includes the following raw materials in percentage by mass: 20% glass powder, Bi4Ti 2.92 W 0.07 Ta 0.01 O 12 80%, the glass powder comprises the following raw materials in percentage by mass: 30% MgO, 20% SiO2, 20% CeO2, 5% Al2O3 and 25% AlF3.

[0052] The preparation process is as follows:

[0053] 1) Raw materials Bi2O3, WO3, Ta2O5 and TiO2 are prepared according to the general formula Bi4Ti 2.92 W 0.07 Ta 0.01 O 12 , mix the ingredients, grind them in a ball mill at a speed of 400r / min for 6 hours, dry them in a 3.3kw ordinary oven at 100℃, and pass through 250 holes / cm 2 The sample was sieved, the temperature was raised to 1080°C at a rate of 8°C / min, and the temperature was kept at 1080°C for 4 hours to obtain frit A.

[0054] 2) Weigh 30 g of MgO, 20 g of SiO2, 20 g of CeO2, 5 g of Al2O3 and 25 g of AlF3, mix, melt, water-cool, grind and sieve to obtain glass powder B.

[0055] 3) Mixing the ingredients: weigh the frit A and the glass powder B in a mass ratio of 80% of the frit A and 20% of the glass powder B, and mix them evenly to obtain a batch C.

[0056] 4) Sodium alginate and deionized water were weighed in a mass ratio of 2% sodium alginate to 98% deionized water to prepare a sodium alginate solution.

[0057] 5) Weigh the sodium alginate solution and ammonium citrate according to the mass ratio of 78% sodium alginate solution and 4% ammonium citrate of ingredient C, add ingredient C, ball mill for 10 hours on a ball mill with a rotation speed of 400r / min, and place the slurry under vacuum conditions for 30 minutes for vacuum degassing. Inject the degassing slurry into a homemade mold, put it into a dryer and control the freezing temperature to -10°C, -30°C, and -50°C, respectively, and freeze it for 7 hours. Take out the mold and demould it quickly, and put it into a freeze dryer for sublimation for 22 hours.

[0058] 6) After drying, the green body is heated to 480°C at a heating rate of 4°C / min in an air atmosphere, and then heated to 850°C at a heating rate of 7°C / min, fired, kept warm for 1 hour, and cooled to obtain a ceramic medium.

[0059] The dielectric properties of the ceramic medium prepared in this embodiment were tested at a test frequency of 1 MHz. The results are shown in Tables 3 and Figure 1 .

[0060] Table 3

[0061]

[0062] Example 4

[0063] A high-toughness ceramic dielectric material includes the following raw materials in percentage by mass: 30% glass powder, Bi4Ti 2.92 W 0.07 Ta 0.01 O 12 70%, the glass powder comprises the following raw materials in percentage by mass: MgO 20%, SiO2 20%, CeO2 20%, Al2O3 20% and AlF3 20%.

[0064] The preparation process is as follows:

[0065] 1) Raw materials Bi2O3, WO3, Ta2O5 and TiO2 are prepared according to the general formula Bi4Ti 2.92 W 0.07 Ta 0.01 0 12 , mix the ingredients, mill them on a ball mill with a speed of 400r / min for 4.5 hours, dry them at 100℃ in a 3.3kw ordinary oven, and pass through 250 holes / cm 2 The sample was sieved, the temperature was raised to 1100°C at a rate of 9°C / min, and the temperature was kept at 1100°C for 2.5 hours to obtain frit A.

[0066] 2) Weigh 20 g of MgO, 20 g of SiO2, 20 g of CeO2, 20 g of Al2O3 and 20 g of AlF3, mix, melt, water-cool, grind and sieve to obtain glass powder B.

[0067] 3) Mixing the ingredients: weigh the frit A and the glass powder B in a mass ratio of 70% of the frit A and 30% of the glass powder B, and mix them evenly to obtain a batch C.

[0068] 4) Sodium alginate and deionized water were weighed in a mass ratio of 2% sodium alginate to 98% deionized water to prepare a sodium alginate solution.

[0069] 5) Weigh the sodium alginate solution and ammonium citrate according to the mass ratio of 80% sodium alginate solution and 5% ammonium citrate of ingredient C, add ingredient C, ball mill for 10 hours on a ball mill with a rotation speed of 400r / min, and place the slurry under vacuum conditions for 30 minutes for vacuum degassing. Inject the degassing slurry into a homemade mold, put it into a dryer and control the freezing temperature to -10°C, -30°C, and -50°C, respectively, and freeze it for 8 hours. Take out the mold and demould it quickly, and put it into a freeze dryer for sublimation for 23 hours.

[0070] 6) After drying, the green body is heated to 500° C. at a heating rate of 5° C. / min in an air atmosphere, and then heated to 860° C. at a heating rate of 8° C. / min, fired, kept warm for 1 hour, and cooled to obtain a ceramic medium.

[0071] The dielectric properties of the ceramic medium prepared in this embodiment were tested at a test frequency of 1 MHz. The results are shown in Tables 4 and Figure 1 .

[0072] Table 4

[0073]

[0074] The dielectric properties of Examples 1-4 were tested using the following testing methods and testing equipment:

[0075] a. Test of dielectric constant ε and loss tanδ

[0076] The capacitance C and dielectric loss tanδ of the capacitor were tested using a HEWLETT PACKARD 4278A capacitance tester (test frequency was 1MHz), and the dielectric constant ε was calculated using the following formula:

[0077]

[0078] Where: C-capacitance of the sample, unit: pF; d-thickness of the sample, unit: cm; D-diameter of the sample after sintering, unit: cm.

[0079] b. Temperature coefficient TCC test (-55℃~180℃)

[0080] The capacitance temperature coefficient of the capacitor was calculated by measuring the change of the capacitance of the sample with temperature using the 6425 WAYKERR bridge, GZ-ESPEC MC-710F high and low temperature chamber and HM27002 capacitor CT / V characteristic tester (test frequency is 1MHz). The calculation formula is as follows:

[0081]

[0082] In the formula: the reference temperature is 25℃, C0 is the capacity at temperature 25℃, and C1 is the capacity at temperature t1.

[0083] c. Fracture toughness test

[0084] The specimens were cut and polished to 25mm in length, 2.5mm in width, and 5mm in height. A 2.5mm deep and 0.5mm wide transverse incision was made at the midpoint of the specimen using a MY-106 dental polishing handpiece. The specimens were then placed on an AGS-10KN universal material testing machine with a span of 15mm. The specimens were loaded at a loading rate of 0.05mm / min using a three-point bending method until they broke. The fracture toughness of the specimen was calculated using the following formula:

[0085]

[0086] Where: K IC is the fracture toughness (MPa·m 1 / 2 ); S, B, w, a represent the loading span, thickness, width and size parameters of the middle crack of the test specimen respectively; P is the concentrated load loaded in the middle; f(a / w) is the shape correction factor of different test specimens. For this specimen, the calculation formula of f(a / w) is:

[0087]

[0088] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.

[0089] The present invention is not intended to be limited to the embodiments shown herein but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A high-toughness ceramic dielectric material, characterized in that: The raw materials include the following mass percentages: glass powder 10-30%, Bi4Ti 2.92 W 0.07 Ta 0.01 O 12 70-90%, the specific preparation steps are: 1) Raw materials Bi2O3, WO3, Ta2O5 and TiO2 are prepared according to the general formula Bi4Ti 2.92 W 0.07 Ta 0.01 O 12 Weigh the ingredients in the chemical stoichiometric ratio, ball mill them, and pass through 120-250 pores / cm 2 Sieve the sample, raise the temperature to 1000-1100℃, keep it warm for 2-4 hours, and obtain frit A; 2) melting MgO 5-40%, SiO2 5-30%, CeO2 5-30%, Al2O3 5-30% and AlF3 5-30% according to mass percentage, cooling with water, grinding and sieving to obtain glass powder B; 3) 10-30% of glass powder B and 70-90% of frit A are mixed according to mass percentage to obtain mix C; 4) preparing a sodium alginate solution by mixing 2% sodium alginate and 98% deionized water according to mass percentage; 5) adding 70-80% by mass of sodium alginate solution and 2-5% by mass of ammonium citrate to ingredient C, ball milling, vacuum degassing, and directional freeze drying; 6) After drying, the green body is slowly heated in an air atmosphere from room temperature to 400-500°C at a heating rate of 2-5°C / min, and then heated from 400-500°C to 830-860°C at a heating rate of 5-8°C / min, and then kept warm for 1 hour, and then cooled to obtain a ceramic medium.

2. A high-toughness ceramic dielectric material according to claim 1, characterized in that: In the step 1), the ball milling time is 4-6 hours, and the ball milling medium is a zirconia ball with a diameter of 1 mm.

3. A high-toughness ceramic dielectric material according to claim 1, characterized in that: The heating rate in step 1) is 7-9°C / min.

4. A high-toughness ceramic dielectric material according to claim 1, characterized in that: The drying time in step 5) is 20-23 hours.